2020
DOI: 10.1093/mnras/staa2275
|View full text |Cite
|
Sign up to set email alerts
|

A survey for variable young stars with small telescopes – III. Warm spots on the active star V1598 Cyg

Abstract: Magnetic spots on low-mass stars can be traced and characterised using multi-band photometric light curves. Here we analyse an extensive data set for one active star, V1598 Cyg, a known variable K dwarf which is either pre-main sequence and/or in a close binary system. Our light curve contains 2854 photometric data points, mostly in V, Rc, Ic, but also in U, B and Hα, with a total baseline of about 4 yr, obtained with small telescopes as part of the HOYS project. We find that V1598 Cyg is a very fast rotator w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Koen ( 2021b ) furthermore showed that a number of K2 CPV light curves can be modelled by mixtures of large circular cool and hot surface spots. Note in this regard that there is support in the literature for the presence of bright spots on late type stars with magnetic fields (Walkowicz & Ha wle y 2009 ;Rice, Strassmeier & Kopf 2011 ;Donati et al 2014 ;Koen 2015 ;Morris et al 2018 ;Froebrich et al 2020 ).…”
mentioning
confidence: 54%
“…Koen ( 2021b ) furthermore showed that a number of K2 CPV light curves can be modelled by mixtures of large circular cool and hot surface spots. Note in this regard that there is support in the literature for the presence of bright spots on late type stars with magnetic fields (Walkowicz & Ha wle y 2009 ;Rice, Strassmeier & Kopf 2011 ;Donati et al 2014 ;Koen 2015 ;Morris et al 2018 ;Froebrich et al 2020 ).…”
mentioning
confidence: 54%
“…One object, 7896 (V1598 Cyg), is situated clearly above the main sequence. This source has no infrared excess and Froebrich et al (2020) concluded that it is most likely a close binary and/or a foreground YSO. Most of the sources have no or only marginal infrared excess.…”
Section: Foreground Ysosmentioning
confidence: 99%
“…We are only aware of two other known periods amongst our periodic variable sample. One is in the YSO list (7181, LkHA 146, Ibryamov et al (2018)) and one in the non-YSO list (7896, V 1598 Cyg, Froebrich et al (2020)). With the one exception from Bhardwaj et al (2019), all published periods agree with the ones found in our analysis.…”
Section: Comparison With Published Periodsmentioning
confidence: 99%
“…We are only aware of two other known periods amongst our periodic variable sample. One is in the YSO list (7181, LkHA 146, Ibryamov et al (2018)) and one in the non-YSO list (7896, V 1598 Cyg, Froebrich et al (2020)). With the one exception from Bhardwaj et al (2019), all published periods agree with the ones found in our analysis.…”
Section: Comparison With Published Periodsmentioning
confidence: 99%